A ANALISIS PENGARUH MODAL KERJA DAN SATUAN JAM KERJA TERHADAP PENDAPATAN PEDAGANG KAKI LIMA DI KECAMATAN TANJUNG REDEB KABUPATEN BERAU: ANALISIS PENGARUH MODAL KERJA DAN SATUAN JAM KERJA TERHADAP PENDAPATAN PEDAGANG KAKI LIMA DI KECAMATAN TANJUNG REDEB KABUPATEN BERAU - Dandy Ahmad Drajat (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2018)
Analysis of the Effect of Working Capital and Working Hours on the Revenue of Street Traders in Tanjung Redeb Sub-District, Berau District. The purpose of this study is to determine the effect of working capital on the income level of street vendors, especially fried sellers in Tanjung Redeb Sub-district, Berau District. Based on the results obtained F count = 66.990 is greater than F table = 3.16, then there is the influence of working capital and working hours on the income of street vendors in Tanjung Redeb Sub-district of Berau Regency